STABILITY ANALYSIS OF GLOBE VALVE USING CLASSICAL TECHNIQUES - ABORISADE DAVID OLUGBENGA; OKELOLA MUNIRU OLAJIDE; ADEWUYI PHILIP ADESOLA (Journal of Engineering Studies and Research)
The importance of globe valve in fluid handling and control cannot be overemphasized. It is useful in oil and gas applications. If globe valve is not properly modelled, its primary purpose of regulation of fluid flow may be defeated. In this work, model of globe valve is developed from basic mechanical principles.  The resulting model is a second order system whose response to a step input signal gives no overshoot. Further stability analysis with bode plot, Nyquist plot and root locus plot give a stable system indicating that the developed globe valve model is suitable for relevant areas of application.